MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN KOLASE BAHAN BEKAS PADA ANAK KELOMPOK B DI PAUD AZ-ZAHRA INSTITUT AHMAD DAHLAN PROBOLINGGO - Latifah; Prasetiya, Benny (LPPM IAD Probolinggo, 2023)
The development of children's fine motor skills at PAUD AZ-ZAHRA Lekok Pasuruan is still weak, this is because the choice of methods and tools used do not attract the child's attention, or perhaps the child is too bored with materials that only use ingredients. crayon. every day So our researchers want to use new methods and materials to present a collage of used materials. This type of research was classroom action research which aims to improve the fine motor skills of group B or 20 children. This research material was prepared through observation and documentation. The results of this research were carried out in two cycles, namely Cycle I and Cycle II. At the same time there was a revival in cycle II. The conclusion of the research is that the development of children's fine motor skills through neck activities made from used materials has increased rapidly. Keywords: Collage, Early childhood education, Fine motor skills